Security risks in social media technologies : safe practices in public service applications - Oxley, Alan.; ScienceDirect eBooks (Oxford : Chandos Publishing, 2013)
Security measures can be used by management, IT staff, and users in participatory/collaborative service provision within the public sector. Security Risks in Social Media Technologies explores this use. Topics are targeted, and issues raised and lessons learnt are analyzed. The book helps the reader understand the risks posed by relevant Web 2.0 applications and gives clear guidance on how to mitigate those risks. The body of the book is concerned with social media, the dominant Web 2.0 technology associated with security in the public sector, and is structured into eight chapters. The first chapter introduces the background for the work; the second covers uses of social media; the third covers relevant security threats; the fourth chapter concerns the security controls applied to the participation-collaboration pattern; the fifth chapter then considers acceptable use practices; the sixth chapter covers participation-collaboration in the context of schools; the seventh chapter shows an alternative way of classifying controls to that given in the fourth chapter; and the final chapter offers a conclusion. Focuses on the security issues of social media, specifically in the public sectorWritten by a leading researcher and practitionerShows best practices for mitigating risk in the use of social media.
1. Web 2.0 and social media -- 2. Non-frivolous uses of social media in the public sector -- 3. Security threats to social media technologies -- 4. Security controls applied to the participation-collaboration pattern -- 5. Acceptable use practices -- 6. Participation and collaboration in K-12 schools -- 7. Mitigating the risks of identity theft and malware -- 8. Conclusion.
Includes bibliographical references (pages 209-227) and index.
Print version record.
Elsevier
Safari Books Online
Keywords: Computer networks -- Security measures; COMPUTERS -- Internet -- Security; COMPUTERS -- Networking -- Security; Computer networks -- Security measures; Soziale Software; World Wide Web 2.0; Datenschutz; Electronic books